Language Proficiency and Use of Interpreters/Translators in Fieldwork: A Survey of US-Based Anthropologists and Sociologists - Sepielak, Katarzyna; Wladyka, Dawid; Yaworsky, William (Multilingua, 2023)
The proficiency in vernacular has long been a methodological ethos pervasive among field researchers and--despite new dynamics of fieldwork--still overshadows discussions related to collaboration with translators and interpreters, which are either marginalized or hidden within the category of a 'research assistant'. The purpose of this study is to take a step beyond anecdotal evidence and explore trends in language proficiency and use of translation services among US based field researchers who had conducted international or domestic studies in an area where a language other than English was present. We conducted the largest-to-date survey on the subject and analyzed 913 responses from faculty at sociology and anthropology programs in the United States. We documented their global fieldwork activity and found only limited proficiency in field languages accompanied by a proliferation of reliance on translators and interpreters, not matching any methodological discussion present in the textbooks and other scholarly sources. We indicate disparities in the use of vernacular and translation services in the post-colonial societies and point out related ethical and methodological concerns. Furthermore, we analyze the researchers' decision-making processes and their general perspectives on the importance of vernacular's knowledge and opinions on the admissibility of translators in the fieldwork.